Evolution of canker severity and stem quality on African mahogany growth - Andressa Ribeiro; Maurício Sangiogo; Rodolfo Molinário de Sousa; Antonio Carlos Ferraz Filho (Pesquisa Agropecuária Brasileira, 2023)
Abstract The objective of this work was to investigate the influence of the qualitative traits canker severity and stem quality on the mean annual increment (MAI) in diameter, total height, and stem height of an African mahogany (Khaya grandifoliola) stand. The study area is located in the state of Minas Gerais, Brazil, where continuous forest inventories were conducted over six years for data collection. Given the nonparametric characteristic of the data, an aligned rank transform analysis of variance was performed for each factor, and the averages were compared by Dunn’s multiple test. There was no significant effect of the interaction between the classes of canker severity and stand age. Increased canker severity has a significant effect on MAI values, causing reductions of 13% in diameter, 11% in total height, and 21% in stem height in trees from the highest canker severity class, when compared with the healthy ones. Age interacts significantly with stem quality, and MAI values tend to be similar in younger trees, differing over time in the oldest ones. In addition, the highest MAI values are recorded in trees with the best stem classification.